Nighlife and Escapism: The Social Reality of Women's Nightlife at Bira Beach Bulukumba - Salehuddin, Salehuddin; Kamaruddin, Syamsu Andi; Adam, Arlin; Utomo, Jepri (Universitas Tanjungpura, 2024)
This research discusses the phenomenon of nighlife and the social reality of women's nighlife in Bira Beach, Bulukumba, South Sulawesi. Nightlife in this tourist area is not only an attraction for tourists but also reflects complex socio-economic dynamics. The presence of night women in Bira Beach is often influenced by life pressures, economic limitations, and lack of access to education and formal employment opportunities. For some women, night work becomes a strategy for survival as well as a space to escape social and family pressures. This phenomenon also functions as a new social space where individuals can express freedom and rebuild self-identity. Using a qualitative approach and an interpretive paradigm, this research reveals the motivations, dynamics of social interaction, and impacts of nightlife on the women involved. The findings show that nightlife at Bira Beach functions not only as a space of escapism but also presents social challenges, including stigma and marginalization. This phenomenon is relevant to sociological studies, particularly in understanding the impacts of globalization, modernization, and the conflict between local cultural values and modern economic needs. A multidimensional approach is necessary to create inclusive solutions, such as socio-economic empowerment, changing societal perceptions, and community-based interventions. Through these measures, women in the nightlife industry are expected to break free from cycles of poverty and social stigma and gain opportunities to improve their quality of life. This study makes a significant contribution to understanding the relationship between nightlife, social escapism, and the economic-cultural dynamics in coastal communities.